Leadership Strategies and Corporate Culture in Improving Competitiveness and Corporate Performance in Bank Syariah Indonesia - Ricky Gumilang Pratama (MultiTech Publisher, 2024)
The banking industry is currently the choice of the community, namely conventional banks and Islamic banks. One of the Islamic banks that is said to have good performance both financially and non-financially. The purpose of this study is to analyze the extent to which variables can have a positive impact. Several studies have different hypotheses regarding these variables. This study uses a quantitative method with path analysis techniques using Structural Equation Modeling (SEM) with the SmartPLS4 program. The results of the hypothesis test show that leadership strategy has a significant effect on increasing competitiveness and company performance. Corporate culture has a significant effect on increasing competitiveness but is not significant in increasing company performance. Competitiveness that has a significant effect on company performance.